1985
DOI: 10.1177/028072708500300107
|View full text |Cite
|
Sign up to set email alerts
|

Human Response to Disasters

Abstract: We first discuss psychological response and coping behavior in disaster situations. We confirm earlier findings that people have a tendency to interpret the signs of danger within their daily context and to underestimate the possibility of a disaster. It is suggested that the repetitive and consistent information would help to induce adaptive responses. The typical coping patterns found were: (1) information gathering behavior, (2) activities closely related to one's family, (3) preventive or protective behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The leader is followed by the other group members in both the evacuation decision and the choice of mobility destination Hence, if the group is indoors during the earthquake, the group's decision to evacuate will be the same as the leader's. In the case where a group evacuates, all group members evacuate at the same time 55 , they wait for the group member who has the longest evacuation delay. Similarly, the individual target destinations of the group members are changed to the target destination of the group's leader.…”
Section: Group Behaviorsmentioning
confidence: 99%
“…The leader is followed by the other group members in both the evacuation decision and the choice of mobility destination Hence, if the group is indoors during the earthquake, the group's decision to evacuate will be the same as the leader's. In the case where a group evacuates, all group members evacuate at the same time 55 , they wait for the group member who has the longest evacuation delay. Similarly, the individual target destinations of the group members are changed to the target destination of the group's leader.…”
Section: Group Behaviorsmentioning
confidence: 99%
“…Relatedly, people are more likely to respond to a warning message if it contains information about what to do to protect themselves (DiGiovanni et al, 2002;Mileti and Darlington, 1997). Warning messages are most effective when they are not only clear but also repeated (Drabek, 1969;Mikami and Ikeda, 1985; and consistent (Christiansen and Ruch, 1980;DiGiovanni et al, 2002;Nigg, 1987). For example, have shown that when the same information is received multiple times from multiple different sources, its impact on risk perception and on people's efforts to obtain further information is maximized (see also Pfister, 2002).…”
Section: Introductionmentioning
confidence: 99%